Productivity improvement via simulation in manufacturing industry - Syed Muhammad Adib, Syed Mohd Zaki (2012)
Productivity improvement effort such as better layout arrangement, minimize the total production cost or maximize the throughput had been given great attentions in today manufacturing industries. However, to execute such improvements involve a big amount of money which normally be the cause that obstruct the improvements. Simulation has become one of the solutions to this problem and rapidly gaining the industry confident nowadays. This study aims to make improvement in terms of the company’s production layout which focusing to the sandwich bread production line. The study is conducted at Roti Temerloh Enterprise, a company which produces products such as sandwich breads, buns and cakes. Being considered as one of the Small and Medium Enterprises (SMEs), cost certainly be the big issues when improvement planning to be considered. Using WITNESS simulation software, the production of the sandwich bread will be modeled and some adjustment then reviewed through the simulation to come up with the improved alternatives layouts. Comparison analysis is carried out and the results show in increased of production up to 265 breads per day for alternative 1 and 581 breads per day for alternative 2 and 3. Machine utilization in term of idle time, busy time and blocked for; Alternative 1 86.69%, 13.49% and 0.49%, Alternative 2 66.49%, 26.82% and 6.69%, Alternative 3 69.64%, 25.04% and 5.32%. From the cost effectiveness analysis, the cost is RM2.06 per unit for Alternative 1 and RM1.49 per unit for Alternatives 2 and 3. Thus the suggested alternative is Alternative 3.